Peran Pembelajaran Berbasis Lingkungan Dalam Meningkatkan Pemahaman Peserta Didik Di MI Cimahi Peuntas Kabupaten Sukabumi - Tintin Handiyati; Siti Qomariyah; Jimmi Kurniawan (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
Human civilization continues to experience development along with the development of knowledge. One of these developments occurred in the industrial sector, most of which call it the industrial era. However, in line with the development of the industry, it also affects the condition of natural resources and the environment, which continues to increase in damage due to the fulfillment of industrial needs. Green education (green education) is an effort to form students who have character, behavior patterns, awareness and care for the environment. The environment is an aspect that is related to many things, including learning. This study uses qualitative methods with data analysis using triangulation so that the data obtained can be validated with other data generated by different data collection methods. The policy regarding environment-based learning in increasing the understanding of students at MI Cimahi Peuntas Sukabumi Regency is contained in the Vision, namely to create a school that is competitive, has quality character and prepares a competitive Islamic generation, and cares for the environment, then describes its derivatives in SK number 75/01/KPTS -KAMAD/02/2017 concerning the Caring and Cultured Environment Movement in Madrasas. Environment-Based Learning at MI Cimahi Peuntas Sukabumi Regency is carried out through the following stages: Identification of learning objectives, Integration of environmental issues in the curriculum, Project-based learning, Outdoor learning, Collaboration with local communities, Cross-disciplinary learning, Reflective learning, and Real action. Then some material related to the learning is: Climate Change, Biodiversity, Management of Natural Resources, Waste and Recycling, Environmental Pollution, Energy and Water Saving, and Ecotourism. Improving Student Understanding Through Environment-Based Learning at MI Cimahi Peuntas Sukabumi Regency is carried out in several ways, namely: Relevance and Context, Direct Experience, Multidisciplinary, Problem Solving, Collaboration and Social Engagement, and Reflection and Evaluation